2014
DOI: 10.1098/rsif.2014.0617
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic frequency for a systems approach to haemodynamic waveform analysis with clinical applications

Abstract: The reductionist approach has dominated the fields of biology and medicine for nearly a century. Here, we present a systems science approach to the analysis of physiological waveforms in the context of a specific case, cardiovascular physiology. Our goal in this study is to introduce a methodology that allows for novel insight into cardiovascular physiology and to show proof of concept for a new index for the evaluation of the cardiovascular system through pressure wave analysis. This methodology uses a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(123 citation statements)
references
References 26 publications
3
120
0
Order By: Relevance
“…Figure 1B shows the decomposition of S and D into two intrinsic frequencies ω 1 and ω 2 respectively: Δω denotes the difference between the two. Previously, 15 we applied the algorithm to clinical data (pressure wave forms) obtained from subjects with established cardiovascular disease as well as from healthy controls. We showed that ω ) corresponded specifically to vascular disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1B shows the decomposition of S and D into two intrinsic frequencies ω 1 and ω 2 respectively: Δω denotes the difference between the two. Previously, 15 we applied the algorithm to clinical data (pressure wave forms) obtained from subjects with established cardiovascular disease as well as from healthy controls. We showed that ω ) corresponded specifically to vascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical monitoring of PWV, while noninvasive and well correlated with insulin resistance, is decidedly impractical. In a recently published study, 15 we applied a novel signalprocessing algorithm, intrinsic frequency method (IFM), to clinical data (pressure wave forms) obtained from subjects with established cardiovascular disease along with healthy controls. The algorithm successfully screened and analyzed an array of cardiovascular pathologies.…”
Section: Pulse Wave Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…IF can be computed using this formula in a fraction of second. Details regarding mathematical formulation of IF method [12], its computational procedure [12], and its convergence/accuracy [19] can be found in previous publications [12,17,19].…”
Section: Intrinsic Frequency Methodsmentioning
confidence: 99%
“…Pahlevan et. al [12] recently introduced a new mathematical method, called the intrinsic frequency (IF) method, that is suitable for the dynamic analysis of coupled physiological systems such as the LV and the arterial network. IF uses an integrative systems approach that considers the LV and arterial network as a coupled dynamical system (LV + arterial tree) that is decoupled upon closure of the aortic valve [13][14][15][16].…”
mentioning
confidence: 99%